Pemanfaatan Media Promosi Pemasaran Digital: Studi Pada Rumah Sakit di Kabupaten Malang - Shofi Nur Rahmah (P3M Politeknik Negeri Malang, 2023)
The rapid development of technology in the digital era makes people cannot be separated from gadgets and social media. It needs to be considered by hospitals as health service providers to participate in utilizing digital marketing in promoting their health facilities. This study aims to determine the level of knowledge of the public relation and marketing staff at Mitra Delima Hospital, Malang and carried out an intervention in the form of digital marketing training. This study used a pre-experimental one group research method with pre and post intervention designs without control. The samples in this study were 25 staff of public relation and marketing. The data in this study were analyzed descriptively. The results of this study indicated that the staff’s knowledge about digital marketing after participating in the training increased. It is proved by the comparison of pre and post-test scores that were given.